2022
DOI: 10.1039/d2ra03407g
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study on the mechanical and electronic properties of energetic molecular perovskites AM(ClO4)3 (A = C6H14N22+, C4H12N22+, C6H14N2O2+; M = Na+, K+)

Abstract: Using the pCOHP method it was revealed the band gap, and the modulus properties are related to the type and strength of the M–O bonds in a series of molecular perovskite high-energetic compounds AM(ClO4)3 (A = C6H14N22+, C4H12N22+, C6H14N2O2+; M = Na+, K+).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…We are aware that permanganates and periodates are prone to explosive reactions. 6,49,50 To evaluate the safety of Tris-HClO 4 , the melting point tests were conducted under ambient conditions using a small amount of Tris-HClO 4 . We observed that it transitions to a liquid state at 494 K without exhibiting any signs of unusual behavior.…”
Section: Resultsmentioning
confidence: 99%
“…We are aware that permanganates and periodates are prone to explosive reactions. 6,49,50 To evaluate the safety of Tris-HClO 4 , the melting point tests were conducted under ambient conditions using a small amount of Tris-HClO 4 . We observed that it transitions to a liquid state at 494 K without exhibiting any signs of unusual behavior.…”
Section: Resultsmentioning
confidence: 99%